Pacing and heat stress independently and differentially effect elite marathon performance - Leslie, E.; Ducharme, J. B.; Coffey, P.; Van Horn, M. L. (Sport Sciences for Health, 2023)
Purpose Pacing strategies and weather conditions can have a large influence on elite marathon race times. The purpose of this study is to evaluate the relationship between elite marathon running performance, heat stress, and pacing while controlling for sex, age, and previous personal best marathon time. We hypothesized slower race times would be evident with greater variations in pacing and higher heat stress.